PERSEPSI MAHASISWI TERHADAP BEAUTY VLOGGER DAN DAMPAKNYA PADA KEPUTUSAN PEMBELIAN MAKE-UP - Maya Suryani; Fitria Rahmi; Nelia Afriyeni (LPPM Politeknik Pratama, 2021)
The study aims to see the effect of college student perception to beauty vlogger on the purchase decision of make-up products. The methods used in this research are quantitative methods, with incidental sampling forms and subjects for this research amounted to 201 college students in the city of Padang. These data are analyzed with simple regression analysis. The results showed that there was an effect of college student perceptions of beauty vlogger on purchasing decisions for make-up products p = 0,000 (p <0.05), which was 22%, meaning that the better the perception of beauty vlogger, the higher the purchasing decision and the remaining 78% is influenced by other variables not examined in this study.